Order Theory of Alloy \(β - \text{CuZn}\) - Tam, Pham Dinh; Tan, Pham Duy; Hoc, Nguyen Quang (Communications in Physics, 2013)
By applying the model of pair interaction, the model of central atom, the method of coordination sphere and the statistical moment method, we calculate the free energy of  β- CuZn ordered alloy and determine the dependence of ordered parameter and lattice constant on pressure and temperature for this alloy. The obtained results have simple analytic, easy to calculate form and our numerical results are in good agreement with the experimental data.